A Novel Structure-Pulse Coupled Model for Quantifying the Column Ductility Demand under Pulse-Like GMs - Zhong, Jian; Yang, Tao; Pang, Yutao; Yuan, Wancheng (Journal of earthquake engineering : JEE, 2022)
A novel model is constructed to investigate the coupling effect of pulse period (T p ) and peak pulse velocity (V p ) on structural demands with the varied fundamental period (T 1 ) under pulse-like ground motions. The Gaussian function is proposed to quantitatively describe the bell-shape curve of column ductility demand in terms of ln(T 1 /T p ). Further investigation reveals that the two critical parameters of Gaussian function, i.e. the height of the curve's peak and the position of the center of the peak, are significantly influenced by V p , and analytically illustrated by Power function and Boltzmann function, respectively. verification of the proposed two-dimensional structure-pulse coupling model exhibits its accuracy and feasibility in predicting the seismic demand conditioned on vector-valued intensity measure ([V p , ln(T 1 /T p )]) under pulse-like ground motion. Moreover, the coupling model can be used to identify and quantify the response regularity, for instance, the phenomenon that the center position of the peak shifts from 1.0 to 0.5 by increasing V p is analytically captured in this study. Lastly, the coupling model is also capable to identify the unfavorable range of structural parameters, which is quite practical for near-fault seismic design and risk assessment.